2010
DOI: 10.1590/s0066-782x2010000300010
|View full text |Cite
|
Sign up to set email alerts
|

O pré-condicionamento isquêmico influencia a contratilidade ventricular na cirurgia sem extracorpórea

Abstract: Background: Ischemic preconditioning is a method that prepares and protects cells to tolerate a long period of ischemia with the least possible injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“… Post-op EF IP and adenosine did not elicit statistically significant EF preservation compared to the control group No difference found in post-op EF and enzymes release in between groups. Incidence of arrhythmias was higher in the IP group but did not reach statistical significance 20 Adenosine IP induced with twice 2 min LAD occlusion followed 3 min reperfusion before the first anastomosis Arrhythmias 20 IP Troponin/CK-MB 20 Control Hong et al ( 2012 ) Circulation Journal, Japan [ 18 ] Prospective controlled randomized trial Seventy OPCAB Lower limb 4 cycles of 5 min ischemia and 5 min of reperfusion before anastomoses (RIPC) and after anastomoses (RIPostC) Troponin release RIPC + RIPostC significantly reduced postoperative serum troponin I levels RIPC + RIPostC decreased postoperative myocardial enzyme elevation by almost half postoperatively in patients undergoing OPCAB 35 RIPC + RIPpostC 35 Control Hong et al ( 2010 )] Anaesth Intensive Care, Korea [ 19 ] Prospective randomized controlled trial 130 OPCAB Upper limb 4 cycles of 5 min ischemia and 5 min of reperfusion after anesthesia Troponin release Troponin release was lower in the RIPC group but was not statistically significant RIPC did not reduce significantly post-operative myocardial enzyme release 65 RIPC 65 Control Succi et al ( 2010 ) Arq Bras Cardiol, Brasil [ 20 ] Prospective controlled randomized trial Forty OPCAB IP induced with twice 1 min LAD occlusion followed 2 min reperfusion before the anastomosis Intra-op EF (measured pulsed Doppler of the descending thoracic aorta) Acceleration of the aortic blood flow with no differences in between groups; IP group maintained left ventricular contractility during the entire procedure while the control group presented significant reduction in left ventricular contractility IP prevented the decrease in left ventricular contractility during off-pump myocardial revascularization surgery 0 IP 20 Control Drenger et al ( 2008 ) Journal of Cardiothoracic and Vascular Anesthesia, Israel [ 21 ] Prospective controlled randomized trial Twenty five OPCAB IP induced with single 5 min LAD occlusion follo...…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“… Post-op EF IP and adenosine did not elicit statistically significant EF preservation compared to the control group No difference found in post-op EF and enzymes release in between groups. Incidence of arrhythmias was higher in the IP group but did not reach statistical significance 20 Adenosine IP induced with twice 2 min LAD occlusion followed 3 min reperfusion before the first anastomosis Arrhythmias 20 IP Troponin/CK-MB 20 Control Hong et al ( 2012 ) Circulation Journal, Japan [ 18 ] Prospective controlled randomized trial Seventy OPCAB Lower limb 4 cycles of 5 min ischemia and 5 min of reperfusion before anastomoses (RIPC) and after anastomoses (RIPostC) Troponin release RIPC + RIPostC significantly reduced postoperative serum troponin I levels RIPC + RIPostC decreased postoperative myocardial enzyme elevation by almost half postoperatively in patients undergoing OPCAB 35 RIPC + RIPpostC 35 Control Hong et al ( 2010 )] Anaesth Intensive Care, Korea [ 19 ] Prospective randomized controlled trial 130 OPCAB Upper limb 4 cycles of 5 min ischemia and 5 min of reperfusion after anesthesia Troponin release Troponin release was lower in the RIPC group but was not statistically significant RIPC did not reduce significantly post-operative myocardial enzyme release 65 RIPC 65 Control Succi et al ( 2010 ) Arq Bras Cardiol, Brasil [ 20 ] Prospective controlled randomized trial Forty OPCAB IP induced with twice 1 min LAD occlusion followed 2 min reperfusion before the anastomosis Intra-op EF (measured pulsed Doppler of the descending thoracic aorta) Acceleration of the aortic blood flow with no differences in between groups; IP group maintained left ventricular contractility during the entire procedure while the control group presented significant reduction in left ventricular contractility IP prevented the decrease in left ventricular contractility during off-pump myocardial revascularization surgery 0 IP 20 Control Drenger et al ( 2008 ) Journal of Cardiothoracic and Vascular Anesthesia, Israel [ 21 ] Prospective controlled randomized trial Twenty five OPCAB IP induced with single 5 min LAD occlusion follo...…”
Section: Reviewmentioning
confidence: 99%
“…Troponin release was lower in the RIPC group but did not reach statistical significance (p = 0.172) [ 19 ]. Succi et al [ 20 ] reported that IP, induced only by 1 minutes of LAD occlusion followed by 2 minutes of reperfusion before anastomosis prevented decrease in left ventricular contractility Hong et al [ 18 ] used both RIPC and postconditioning (PostC) in a cohort of 35 OPCAB patients. Ischemic remote preconditioning and PostC were elicited with 4 cycles of 5 minutes of ischemia and 5 minutes of reperfusion of the lower limb before and after anastomosis.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations